Necessity of the Risk Management Implementation in the Framework of the Socially Responsible Entrepreneurship (UNWE Yearbook, 2017)
The dynamic development of the global business environment raises a number of issues that require that managers should consider the possible negative impact of their daily decision-making. The erroneous decisions affect not only a company's stakeholders but also its further development. Therefore sustainable growth of the business requires that company managers should be able to anticipate potential risks, manage change and thus avert a possible crisis. This paper aims to make an analysis of the state of affairs with regard to corporate social responsibility and risk management abroad. It also aims to assess the flaws in implementing risk management in the framework of the socially responsible entrepreneurship. The conclusions arrived at suggest that a successful implementation of risk management in the enterprises is mainly dependent on managers' attitudes to risk and in the appropriately adjusted corporate culture.